Γδ T cells and inflammatory skin diseases. Issue 1 (27th August 2020) - Jee, Mia Hamilton; Mraz, Veronika; Geisler, Carsten; Bonefeld, Charlotte Menné
Abstract: Approximately 25% of the population suffers from skin diseases. The most common forms of skin diseases are the inflammatory skin diseases such as allergic contact dermatitis, psoriasis, and atopic dermatitis. These diseases are described as T cell–mediated diseases induced by either allergens or autoantigens. Classically, the focus has been on the role of αβ T cells, but it is becoming increasingly clear that γδ T cells play a central role in inflammatory skin diseases. In particular, an important role of IL‐17A–producing γδ T cells in these inflammatory skin diseases has been shown in various disease models in mice. Interestingly, various epidermal proteins, which appear to be linked to inflammatory conditions in the skin by yet undescribed mechanisms, are expressed by specific subsets of thymic epithelial cells and mutations in these proteins seem to affect γδ T cell development. The focus of this review is how mutations in epidermal proteins affect γδ T cell development and how γδ T cells, and in particular of IL‐17A–producing γδ T cells, contribute to inflammatory skin diseases such as allergic contact dermatitis, psoriasis, and atopic dermatitis.